Evidence for the existence of self-reactive human B lymphocytes. - Primi, D (1977)
Supernatants from human tonsil cells cultured in the presence of the PBAs, LPS and F (ab)2 monomers of rabbit anti-human beta2-microglobulin were found to have a complement-dependent cytotoxic activity to tonsil cells of the same donors. A direct toxic effect of the PBAs on the target cells was excluded by controls. Therefore the most likely explanation for this finding is that human lymphocytes contain a subpopulation of self-reactive B cells which can be triggered by PBAs to release antibodies to self-antigens. The implications of this finding for the understanding of infections accompanied by auto-immune phenomena are discussed.